The application of investigative techniques in the detection and prosecution of economic crimes: best practices and challenges in international cooperation - Bermúdez-Bermúdez, Yonni Albeiro; Henao Bohórquez, Mauricio (DIXI, 2025)
In an increasingly globalized world, transnational economic crime poses a significant challenge to criminal justice systems worldwide. The effective application of financial investigation techniques plays a crucial role in detecting, investigating, and subsequently sanctioning economic crimes, such as private corruption and money laundering. This paper will examine best practices in the use of financial investigation techniques and the challenges associated with international cooperation in combating economic crime in Latin America. Through a qualitative approach, the results demonstrate that international cooperation is essential for gathering evidence, tracking illicit money, and extraditing suspects. However, challenges arise around extradition and the transfer of digital evidence between national and international agencies, which have provided lessons learned and recommendations to strengthen international cooperation in the fight against economic crime.